Targeting millers to improve rice marketing in Uganda - Twine, Edgar E.; Adur-Okello, S.E.; Mujawamariya, Gaudiose; Ndindeng, S.A. (Emerald Publishing Limited, 2021)
Purpose Improving milling quality is expected to improve the quality of domestic rice and hence the competitiveness of Uganda's rice industry. Therefore, this study aims to assess the determinants of four aspects of milling, namely, choice of milling technology, millers' perceptions of the importance of paddy quality attributes, milling return and milling capacity.